EMPREGO DE RECURSOS POÉTICOS PARA A CONSTRUÇÃO DE TEXTOS NÃO-LITERÁRIOS - Canolla, Clemira (Intercâmbio, 2010)
This work discusses the teaching of writing abilities in Portuguese and argues that it is possible to students in any level to develop their capacities of writing non-literary texts with an approach to poetic linguistic resources, mainly the metaphor.